Pengaruh literasi keuangan, pemahaman SIA, dan lingkungan sosial terhadap mitigasi penipuan keuangan pada penggunaan transaksi digital mahasiswa akuntansi Universitas Sam Ratulangi Manado - Supu, Inka Shefrani; Karamoy, Herman; Tangkuman, Steven J. (Manajemen Bisnis dan Keuangan Korporat, 2025)
This study investigates the influence of financial literacy, understanding of accounting information systems (AIS), and social environment on financial fraud mitigation in the use of digital transactions among Accounting students at Sam Ratulangi University, Manado. The increasing adoption of digital financial services by students has heightened their exposure to potential fraud risks. This research employs a quantitative approach with survey data collected from 267 respondents. Multiple linear regression analysis is applied to test the hypotheses. The results reveal that financial literacy and social environment significantly affect financial fraud mitigation, while understanding of AIS shows no significant effect. Simultaneously, the three variables collectively influence students’ ability to mitigate financial fraud in digital transactions. These findings provide theoretical and practical implications for higher education institutions, regulators, and financial service providers to strengthen digital financial education and preventive measures against fraud.